A nuclear‐encoded chloroplast‐targeted S1 RNA‐binding domain protein affects chloroplast rRNA processing and is crucial for the normal growth of Arabidopsis thaliana. (15th June 2015) - Han, Ji Hoon; Lee, Kwanuk; Lee, Kwang Ho; Jung, Sunyo; Jeon, Young; Pai, Hyun‐Sook; Kang, Hunseung
Summary Despite the fact that a variety of nuclear‐encoded RNA‐binding proteins (RBPs) are targeted to the chloroplast and play essential roles during post‐transcriptional RNA metabolism in the chloroplast, the physiological roles of the majority of chloroplast‐targeted RBPs remain elusive. Here, we investigated the functional role of a nuclear‐encoded S1 domain‐containing RBP, designated SDP, in the growth and development of Arabidopsis thaliana. Confocal analysis of the SDP‐green fluorescent protein revealed that SDP was localized to the chloroplast. The loss‐of‐function sdp mutant displayed retarded seed germination and pale‐green phenotypes, and grew smaller than the wild‐type plants. Chlorophyll a content and photosynthetic activity of the sdp mutant were much lower than those of wild‐type plants, and the structures of the chloroplast and the prolamellar body were abnormal in the sdp mutant. The processing of rRNAs in the chloroplast was defective in the sdp mutant, and SDP was able to bind chloroplast 23S, 16S, 5S and 4.5S rRNAs. Notably, SDP possesses RNA chaperone activity. Transcript levels of the nuclear genes involved in chlorophyll biosynthesis were altered in the sdp mutant. Collectively, these results suggest that chloroplast‐targeted SDP harboring RNA chaperone activity affects rRNA processing, chloroplast biogenesis and photosynthetic activity, which is crucial for normal growth of Arabidopsis.